Nonalcoholic Fatty Liver Disease and Chronic Kidney Disease: A Review of Links and Risks - Cheung A (Dove Medical Press, 2021)
Amanda Cheung, Aijaz Ahmed Division of Gastroenterology and Hepatology, Stanford University School of Medicine, Stanford, CA, USACorrespondence: Amanda CheungDivision of Gastroenterology and Hepatology, Stanford University School of Medicine, 750 Welch Road, Suite 210, Stanford, CA, 94304, USATel +1 650-498-6080Fax +1 650-498-5692Email cheungac@stanford.eduAbstract: Nonalcoholic fatty liver disease and chronic kidney disease are both chronic conditions with rapidly increasing prevalence and incidence worldwide that have led to a significant burden on health-care systems. The association between these two disease entities is partly attributed to shared cardiometabolic comorbidities including diabetes, hypertension, obesity, and metabolic syndrome. However, independent of these overlapping risks, there are increased rates and more severe CKD in NAFLD patients. Conversely, more progressive NAFLD is seen with advanced stages of kidney injury. In addition to overlapping risk factors, shared pathogenic mechanisms suggest these two disease entities may resemble different manifestations of a single underlying disease process.Keywords: nonalcoholic fatty liver disease, chronic kidney disease, mortality, metabolic syndrome, gut-liver axis, gut-kidney axis, liver-kidney axis